1974
DOI: 10.1203/00006450-197412000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Glycine-Serine Interconversion in Cultured Human Fibroblasts by Products of Isoleucine Catabolism

Abstract: Pediat. Res. 8: 941-945 (1974) Glycine serine isoleucine tiglic acid

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1978
1978
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 9 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…However, even when using F 10, the same medium as that of Hillman et al we were unable to detect significant activity. In a later publication (12), the same group studied the glycine/serine interconversion in a similar set-up and demonstrated that incubation with both isoleucine and tiglic acid inhibited this reaction, and they suggested that the inhibition of serine hydroxymethyl-transferase caused ketotic hyperglycinemia. However, this is in disagreement with several earlier publications (6,27,29), which all demonstrated that there are deficiencies of the glycine cleavage system and not of serine hydroxymethyltransferase in patients with ketotic hyperglycinemia.…”
Section: Discussionmentioning
confidence: 99%
“…However, even when using F 10, the same medium as that of Hillman et al we were unable to detect significant activity. In a later publication (12), the same group studied the glycine/serine interconversion in a similar set-up and demonstrated that incubation with both isoleucine and tiglic acid inhibited this reaction, and they suggested that the inhibition of serine hydroxymethyl-transferase caused ketotic hyperglycinemia. However, this is in disagreement with several earlier publications (6,27,29), which all demonstrated that there are deficiencies of the glycine cleavage system and not of serine hydroxymethyltransferase in patients with ketotic hyperglycinemia.…”
Section: Discussionmentioning
confidence: 99%
“…Biochemically, the phenotype of human patients was accurately emulated, as illustrated by the types of metabolites that were increased and the extent of their elevation. For example, MMA levels in the urine were detected in a range comparable with human mut Ϫ patients (35), whereas glycine, thought to be increased by inhibition of the intramitochondrial glycine cleavage enzyme caused by accumulated organic acids or their CoA esters (36), was found at high levels in our mice, similar to the description in the first MMAuria patients (37). Further, we found elevated levels of odd chain fatty acids, most likely as a consequence of increased C3, which is used as a primer in fatty acid synthesis (6,23,38,39).…”
Section: Novel Mouse Models Recapitulate Clinical and Biochemicalmentioning
confidence: 99%
“…Various products which accumulate because of the primary metabolic defect have been shown to alter glycine metabolism (Hillman et aI., 1973;Hillman and Otto, 1974;Ho and Hillman, 1974). The defect in the nonketotic syndromes is thought to involve directly the metabolism of glycine.…”
Section: Cytoplasmic Poolmentioning
confidence: 99%